Geology of the San Colombano hill, a Quaternary isolated tectonic relief in the Po Plain of Lombardy (Northern Italy). Issue 2 (13th November 2018) - Zuffetti, Chiara; Bersezio, Riccardo; Contini, Daniele; Petrizzo, Maria Rose
ABSTRACT: The 1:10, 000 geological map of the San Colombano hill covers 60 km 2 in the Po Plain, south of Milan. The new and the historical surface geological data-sets are managed by a GeoDB aiming to contribute to re-interpret the Quaternary evolution at the Po Plain-Northern Apennine border. On the hill, the Calabrian shallow marine San Colombano Fm. unconformably overlies the truncated deeper-marine Miocene formations, up-thrusted by the external fronts of the Apennine Emilian Arc during Mio-Pliocene. Late Pleistocene alluvial units rest in unconformity above the marine succession both on the uplifted hilltop and on the surrounding plain. Fault-related offset of Late Pleistocene units, stratigraphic and morpho-structural evidences (facets, relic surfaces and drainage patterns), document the Quaternary tectonic history. Early to Middle Pleistocene ongoing thrust-folding at the northernmost buried reaches of the Emilian Arc was followed by Latest Pleistocene-Holocene transtension, possibly relating to the NNE striking Pavia-Casteggio lateral ramp.